Zinc glycerolate as a novel heterogeneous catalyst for the synthesis of fatty acid methyl esters - Reinoso, Deborath Mariana (2014)
In this work, zinc glycerolate (ZnGly) is studied as a new catalyst for an environmentally friendly production of biodiesel. The solid was prepared by a simple procedure, characterized and studied in the transesterification of soybean oil with methanol. ZnGly was able to convert soybean oil into fatty acid methyl esters with 66–76% yield and up to 95–97% triglyceride (TG) conversion in the 100–140 °C reaction temperature range studied. The catalyst showed a long life and could be reused for five catalytic cycles without deactivation or selectivity loss. The catalyst exhibited good tolerance toward 0.5 wt.% water, without important changes in the TG conversion, but with a 23% decrease in FAME yield. In the presence of 10 wt.% fatty acids, ZnGly showed an almost complete TG conversion with an increase in FAME yield of 51% (93% FAME selectivity at 50 min reaction time). At 140 °C and in acid oil, ZnGly can be easily transformed into Zn carboxylate and partially re-generated in the presence of glycerol.